Morfofonemik Bahasa Indonesia pada Kata Serapan Bahasa Inggris yang Berawalan Fonem Voiceless: Kajian Teori Optimalitas - Ferdiansyah, Irfan; Wagiati, Wagiati; Wahya, Wahya (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study analyzes the morphophonemic prefix me- on English loanwords in Indonesian language. The approach used to dissect the problem is the Optimality Theory. The method used is a qualitative method with descriptive. The source used in this study is the corpus ind_mixed_2013 in the Corpora Collection Leipzig, and the dictionary source used is the dictionary of Alan M. Stevens and A. Ed. Schmidgall-Tellings entitled A Comprehensive Indonesian-English Dictionary, Second Edition. The purpose of this study is to find the optimal candidate produced by the speaker and find out the relationship between the optimal candidate and the candidate with the most frequency in the corpus. The results obtained in this study show that the candidates most often formed by BI speakers are candidates who have experienced nationalization [n], and [ŋ]. Then, BI speakers have become accustomed to using optimal candidates, except for absorption words that begin with the phonemes /p/, /s/, and /k/.